2007
DOI: 10.1111/j.1744-313x.2007.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐based typing of a novel HLA‐DRB1*04 allele, DRB1*0461, in a Taiwanese volunteer marrow donor

Abstract: We report here a novel HLA-DRB1 allele, DRB1*0461, discovered in a Taiwanese volunteer marrow donor. The new sequence has nucleotide variation at positions 260 (C-->A) and 261 (C-->G), i.e. codon 58, as compared to DRB1*0408. Nucleotide change caused an amino acid substitution from alanine to glutamic acid. We believe that the gene conversion took place between DRB1*0405 and DRB1*1101 based on sequence homology and gene frequency in population studies. In comparison to DRB1*0405, DRB1*0461 has two amino acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…We estimate the frequency of DRB1*04:05:14 is about 1 in 20 000 to 1 in 30 000 based on our SBT typing experience. Similar to the DRB1*04:61 allele that we discovered in Taiwanese (Chen et al ., ), DRB1*04:05:14 may be considered as one of the uncommon DRB1*04 alleles detected in Taiwanese.…”
Section: Introductionmentioning
confidence: 94%
“…We estimate the frequency of DRB1*04:05:14 is about 1 in 20 000 to 1 in 30 000 based on our SBT typing experience. Similar to the DRB1*04:61 allele that we discovered in Taiwanese (Chen et al ., ), DRB1*04:05:14 may be considered as one of the uncommon DRB1*04 alleles detected in Taiwanese.…”
Section: Introductionmentioning
confidence: 94%
“…Genomic DNA typing of HLA-A, -B, -C and -DRB1 loci were first performed using the Dynal Reli SSOP (sequence-specific oligonucleotide probe) HLA-A, -B, -C and -DRB1 Typing Kits (Dynal Biotech, Bromborough, Wirral, UK). For sequence-based typing (SBT), exons 2 and 3 for class I and exon 2 for class II were sequenced to verify rare or novel alleles as described previously [1][2][3][4][5]. Serological investigation of WBC surface antigen was performed according to the standard NIH microlymphocytotoxicity test in Terasaki microtitre wells using either eosin dye exclusion or fluorescence staining methods or both.…”
Section: Methodsmentioning
confidence: 99%
“…In our routine, HLA typing exercise on Taiwanese unrelated volunteer bone marrow stem cell donors from 2010 to 2012, we found eight individuals bearing A*02:28. Our SBT (sequence-based typing) protocol (Chen et al, 2007(Chen et al, , 2008a(Chen et al, ,b, 2009(Chen et al, , 2010 confirmed the DNA sequence of A*02:28, in exons 2 and 3, is identical to the sequence of A*02:06:01 except a nucleotide at residue 238 where G was replaced by A. The DNA sequence of A*02:28 varies with the sequences of A*02:01:01:01, A*02:03:01 and A*02:07:01 with 3, 6 and 4 nucleotides, respectively ( Table 1).…”
Section: Introductionmentioning
confidence: 99%